2003
DOI: 10.1039/b304707e
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio study of the binding of Trichostatin A (TSA) in the active site of Histone Deacetylase Like Protein (HDLP)

Abstract: Histone deacetylase (HDAC) inhibitors have recently attracted considerable interest because of their therapeutic potential for the treatment of cell proliferative diseases. An X-ray structure of a very potent inhibitor, Trichostatin A (TSA), bound to HDLP (an HDAC analogue isolated from Aquifex aeolicus), is available. From this structure, an active site model (322 atoms), relevant for the binding of TSA and structural analogues, has been derived, and TSA has been minimized in this active site at HF 3-21G* lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 46 publications
(30 reference statements)
4
19
0
1
Order By: Relevance
“…34,35 This is further supported by ab initio calculations suggesting the existence of a functional inner HisAsp charge transfer relay system. 36 Mutation of zinc ligand His182 completely abolishes activity (data not shown), confirming previous results which indicate an essential role of the enzyme-bound zinc cation. 17 Mutation of the active site tyrosine (Tyr312) was also shown to abolish catalytic activity supporting the view that this residue has an important function in the catalytic mechanism (C.H.…”
Section: Catalytic Mechanism Of Class 2 Hdacssupporting
confidence: 91%
See 1 more Smart Citation
“…34,35 This is further supported by ab initio calculations suggesting the existence of a functional inner HisAsp charge transfer relay system. 36 Mutation of zinc ligand His182 completely abolishes activity (data not shown), confirming previous results which indicate an essential role of the enzyme-bound zinc cation. 17 Mutation of the active site tyrosine (Tyr312) was also shown to abolish catalytic activity supporting the view that this residue has an important function in the catalytic mechanism (C.H.…”
Section: Catalytic Mechanism Of Class 2 Hdacssupporting
confidence: 91%
“…A major difference found between FB188 HDAH, HDLP and HDAC8 lies within the connecting region between a1 and a3 (amino acid residues [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. In both crystal forms of FB188 HDAH these regions make contacts to another molecule of the asymmetric unit thus stabilizing the structure; in solution this part may be flexible and may change conformation upon binding to or interacting with another protein.…”
Section: Comparison With Class 1 Hdac Structuresmentioning
confidence: 99%
“…Crystallographic studies have shown a zinc-dependent deacetylation catalyzed by HDLP (21). TSA mimicking the acetylated lysine has been shown to chelate the zinc in the catalytic pocket of HDLP by its hydroxamic acid (44). Our computational simulation revealed that TSA also nicely packs into the catalytic pocket of mammalian HDAC2 (Fig.…”
Section: Discussionmentioning
confidence: 80%
“…In relation to the importance of the enzymeinhibitor environment in zinc coordination, Vanommeslaeghe et al have reported that more reliable force field parameters can be obtained with geometry optimization and population analysis on an extended model system at a modest level of theory [42]. Therefore, we carried out semiempirical PM3 and AM1 calculations with the MOPAC program as an effort to improve the potential parameters for the active site zinc complex of HDLP.…”
Section: Force Field Designmentioning
confidence: 99%